PENGARUH KONSELING SLEEP HYGIENE DALAM MENINGKATKAN KUALITAS TIDUR ANAK USIA 3-24 BULAN - Fitri Wahyuni; Rini Rahmayanti; Nurleny Nurleny; Sri Wahyuningsih; Bayu Wandira; Nur Nilam Sari (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Sleep problems in childhood have been found to be associated with memory and learning impairments, irritability, difficulties in mood modulation, attention and behavioral problems, hyperactivity and impulsivity. Short sleep duration has been found to be associated with overweight and obesity. This research describes the protocol of a behavioral intervention planned to promote healthier sleep in infants. Methods: The study is a 1:1 parallel group single-blinded randomized controlled trial enrolling a total of 24 infants at 3-24 months of age. The main eligibility criterion is the infant’s sleep lasting on average less than 15 h per 24 h (daytime and nighttime sleep). The main outcome assessed is the between group difference in average nighttime self-regulated sleep duration (the maximum amount of time the child stays asleep or awake without awakening the parents), at ages 6, 12 and 24 months, evaluated by means of activity diary records and questionnaires. Result: The negative impact of inadequate and insufficient sleep on children’s physical and mental health are unquestionable, as well as its impact on cognitive function, academic performance and behavior. It is hoped that this study will demonstrate a beneficial effect on children's sleep behavior.